2022
DOI: 10.1111/apt.17165
|View full text |Cite
|
Sign up to set email alerts
|

Extrahepatic morbidities and mortality of NAFLD: an umbrella review of meta‐analyses

Abstract: Background: Nonalcoholic fatty liver disease (NAFLD) has reached pandemic proportions currently and may contribute to multiple extrahepatic outcomes. Aim:To comprehensively summarise evidence of associations between NAFLD and risk of extrahepatic outcomes. Methods:We conducted an umbrella review. We searched PubMed, Web of Science and Cochrane database from inception to 27 November 2021. Results:We included 22 meta-analyses with 374 original studies in our analysis.Subjects with NAFLD had an increased risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 69 publications
1
24
0
3
Order By: Relevance
“…This is in striking contrast with HCC where the most advanced stages of liver fibrosis are associated with an increasing risk of disease [20,21]. Finally, an umbrella meta-analysis by Yi et al [22] based on the scrutiny of 39 published meta-analyses results found that individuals with NAFLD exhibited an increased risk of the following extra-hepatic cancers: thyroid, extra-hepatic and intra-hepatic cholangiocarcinoma, pancreatic, esophago-gastric, urinary tract, breast, and lung. The entity of this risk, however, ranged, based on various cancer types, from hazard ratio (HR) 1.25 for lung cancer to HR 2.63 for thyroid cancer.…”
Section: Methods Findings Conclusionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is in striking contrast with HCC where the most advanced stages of liver fibrosis are associated with an increasing risk of disease [20,21]. Finally, an umbrella meta-analysis by Yi et al [22] based on the scrutiny of 39 published meta-analyses results found that individuals with NAFLD exhibited an increased risk of the following extra-hepatic cancers: thyroid, extra-hepatic and intra-hepatic cholangiocarcinoma, pancreatic, esophago-gastric, urinary tract, breast, and lung. The entity of this risk, however, ranged, based on various cancer types, from hazard ratio (HR) 1.25 for lung cancer to HR 2.63 for thyroid cancer.…”
Section: Methods Findings Conclusionmentioning
confidence: 98%
“…Principal modifiers and putative pathomechanisms involved in the association of NAFLD and MAFLD with extra-hepatic cancers. This illustration, based on published studies[18,19,[22][23][24][29][30][31][32], highlights the knowns of this topic. However, our understanding of this complex scenario is far from complete…”
mentioning
confidence: 87%
“…A recent umbrella review examined the associations of NAFLD with the risk of developing CKD stage ≥3 and other extrahepatic adverse outcomes [ 41 ]. Notably, the authors reported a hazard risk for incident CKD (pooled random-effects HR, 1.42; 95% CI 1.33–1.52) that was identical to that reported by the meta-analysis by Mantovani et al [ 37 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Due to the similarity in pathogenesis, MAFLD is often associated with other lifestyle-related disorders such as hypertension, dyslipidemia, and most importantly T2DM, which significantly increases cardiovascular disease (CVD). MAFLD has also been found to be associated with excess risk of extrahepatic cancers, gallstones, gastro-oesophageal reflux disease, hypothyroidism, urolithiasis, chronic kidney disease (CKD), depression and worse maternal and foetal outcomes during pregnancy[ 2 ]. MAFLD is also associated with a substantial increase in cardiovascular morbidity and mortality, with a 3.5 times higher risk of heart failure and 1.93 times excess risk of all-cause CVD mortality as per recent study data in patients with T2DM[ 3 ].…”
Section: Introductionmentioning
confidence: 99%